2022
DOI: 10.32479/ijefi.13328
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Electric Vehicle Adoption: An Integrated Framework for Investigating the Antecedents of Perceived Value and Purchase Intent

Abstract: Due to political instabilities, limited non-renewable resources and international conflicts, the energy industry has been subject to high volatilities in the last few years. This had negative effects on many developing economies, namely those importing most of their energy needs from other countries (i.e., Morocco). More recently, the high increases in energy prices have renewed interests and discussions related to the adoption of electric vehicles. The current study aims to examine Moroccan consumers’ percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Relative advantage is an important factor in predicting a customer's intention to purchase. Various studies have found a significant positive relationship between the two (Hsbollah and Idris, 2009;Rogers, 2003;Loudiyi et al, 2022). According to Aziz et al (2015) and Rahim and Amin (2011), relative advantage positively affects customer's intention to adopt Islamic Takaful products.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Relative advantage is an important factor in predicting a customer's intention to purchase. Various studies have found a significant positive relationship between the two (Hsbollah and Idris, 2009;Rogers, 2003;Loudiyi et al, 2022). According to Aziz et al (2015) and Rahim and Amin (2011), relative advantage positively affects customer's intention to adopt Islamic Takaful products.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…To investigate the antecedents of financial literacy and financial well-being, the SEM is used (Henseler et al, 2009). The partial least squares technique was used as it takes into consideration the early stage of theoretical advancement and the complexity of the conceptual model (Loudiyi et al, 2022). First, the model is assessed in terms of indicator reliability, construct reliability, convergent validity, and discriminant validity.…”
Section: Assessment Of Measurement Modelmentioning
confidence: 99%